A VCO with Wide Tuning Range and Output Switch for Pulsed Frequency Modulated UWB Signal Generation - Weigel, Robert; Eßwein, Alexander (German Microwave Conference, 2011)
This paper describes a VCO with 30% tuning range and integrated output switch, used for the generation of pulsed ultra-wideband signals in an FMCW radar system. The system concept is shown. The VCO with switch has an unmatched single-endedly measured output power of -21 dBm over the whole tuning range of 6.4 GHz to 8.6 GHz with a total of 31.8 mA bias current consumption.
elib2cris::1512001600,weigel2011a
Keywords: BiCMOS integrated circuits; CW radar; FM radar; MMIC; FMCW radar system; pulsed ultrawideband signal